An Historical Account of the Black Empire of Hayti - Rainsford, Marcus (Duke University Press, 2013)
As the first complete narrative in English of the Haitian Revolution, Marcus Rainsford's An Historical Account of the Black Empire of Hayti was highly influential in establishing nineteenth-century world opinion of this momentous event. This new edition is the first to appear since the original publication in 1805. Rainsford, a career officer in the British army, went to Haiti to recruit black soldiers for the British. By publishing his observations of the prowess of black troops, and recounting his meetings with Toussaint Louverture, Rainsford offered eyewitness testimonial that acknowledged the intelligence and effectiveness of the Haitian rebels. Although not an abolitionist, Rainsford nonetheless was supportive of the independent state of Haiti, which he argued posed no threat to British colonial interests in the West Indies, an extremely unusual stance at the time. Rainsford's account made an immediate impact upon publication, being widely reviewed and translated.